2017
DOI: 10.1038/s41598-017-00480-6
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Pulsed Plasma Induces Cell Death in Photosynthetic Organs via Intracellularly Generated ROS

Abstract: The toxicity of atmospheric-pressure pulsed plasma on plant leaf tissues is studied. A nanosecond-pulsed plasma jet is applied to Arabidopsis thaliana leaves. In case of cotyledon, cell death is induced by treatment of only a few seconds. Cell death is also induced in the adult leaf by only 5 seconds of plasma treatment. Plasma induced reactive oxygen species (ROS) accumulation across the tissues within plasma-treated area. Plasma also induced direct physical damage to epidermis tissue of treated area but mere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Transport also depends on the life stage of the plant since ozone can be taken up through the stomata in the leaves. Seol et al [149] observed an accumulation of ROS in chloroplasts, and suggested that through the micropores, ROS can travel down further into the plant tissue, from the epidermis into the mesophyll but if too potent, chloroplast degradation occurs.…”
Section: Ros Entry and Involvement In Seed Developmentmentioning
confidence: 99%
“…Transport also depends on the life stage of the plant since ozone can be taken up through the stomata in the leaves. Seol et al [149] observed an accumulation of ROS in chloroplasts, and suggested that through the micropores, ROS can travel down further into the plant tissue, from the epidermis into the mesophyll but if too potent, chloroplast degradation occurs.…”
Section: Ros Entry and Involvement In Seed Developmentmentioning
confidence: 99%
“…This suggests that high-intensity plasma treatments may cause the inhibitory effects on fungal cellular processes, which may be related to the concentration of ROS and NOx produced by plasma. With the increase in the number and intensity of the plasma treatments, the ROS and NOx concentrations in the media increase continuously, which will induce cell death [ 44 ]. Possibly, there is a plasma dose threshold for the activation of the enzyme production.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, germination was inhibited significantly by a treatment of 50 V input for 9 s [ 6 ]. The reason may be that this treatment exceeded the high dose for living tissue [ 8 ], and excessive ROS produced by plasma may cause damage to seeds [ 49 ].…”
Section: Discussionmentioning
confidence: 99%